Interaction of human fibrinogen receptor (GPIIb-IIIa) with decorsin - YANG Jie; ZHAN Chen-yang; DONG Xian-chi; YANG Kun; WANG Fu-xiang (Acta Pharmacologica Sinica, 2016)
AIM: To build up the structure of human fibrinogen receptor GPIIb-IIIa, subsequently combined with its antagonist decorsin, and to investigate the interaction between decorsin and its receptor GPIIb-IIIa at the molecular level. METHODS: A three-dimensional (3D) molecular model of human fibrinogen receptor GPIIb-IIIa was generated by InsightII, a distance geometry-based homologous modeling package. The structure of human fibrinogen receptor GPIIb-IIIa was built by the InsightII/Homology module using the corresponding of integrin alphaVbeta3 (PDB filecode 1JV2) as the template. Then the primary structures were optimized by energy minimization. Subsequently the structural model was docked with its antagonist decorsin (PDB filecode 1dec). RESULTS: A good substrate-receptor interaction model was achieved. The interaction sites with decorsin converge at domain 8 (betaA domain of beta3 subunit) of GPIIb-IIIa. The direct interatomic contacts were made between 16 GPIIb/IIIa residues and 10 decorsin amino-acid residues. These included van der Waals contacts, electrostatic interaction, hydrogen bond, and salt bridge. Residues in contact were concentrated in four dispersed regions of human GPIIb-IIIa: the RGD reaction motif (118-132 of GPIIIa), the span from 210 to 213 of GPIIIa, Thr182 residue and Asp251 residue of GPIIIa; and they were distributed over five segments of decorsin: Asp10 residue, Asn18 and Lys19 residues, Arg28 residue, RGD motif, and Asp35-Pro36-Tyr37 segment. CONCLUSION: This complex model plays an important role in development and research of some new drugs, especially a new guided fusion-type fibrinogen receptor antagonist.